Epistemologi Tafsir Karya Ahmad Hassan: Studi Komparatif Tafsir Al-Hidayah dan Tafsir Al-Furqan - Anggun Puspita Ningrum; Masruchin; Beko Hendro (JOM, 2023)
This article investigates the interpretation of Juz 30 in Tafsir Al-Hidayah and Tafsir Al-Furqan by Ahmad Hassan. The two commentaries are comparatively analyzed to produce a clear mapping of the background of the writing of Juz 30 by Ahmad Hassan in two different versions. The research approach used a qualitative method based on literature data, with a focus on content analysis. In the analytical framework, this study adopts Muhammad Abid Al-Jabiri's epistemological trilogy theory to explore and analyze Ahmad Hassan's thoughts in the interpretation of Juz 30. The results show that there are various factors that motivate the writing of these two versions of tafsir, which are influenced by internal pressures from the PERSIS organization and social conditions during that period. Both Ahmad Hassan's interpretations use the ijmali method, but with different approaches; Al-Hidayah emphasizes the adabi ijtima'I style, while Al-Furqan tends to focus on the lughowi style. The sources of interpretation used in both books are closer to history and hadith; therefore, they can be classified as tafsir bil ma'tsur with bayani epistemological reasoning. The study confirms that the variations in the interpretation of Juz 30 by Ahmad Hassan can be explained by the complex interaction between internal organizational factors and the social context at the time of writing.